Penerapan Media Pembelajaran Berbasis Aplikasi History Room Untuk Meningkatkan Aktivitas Belajar Siswa SMP MINQU - Santoso, Narto Puji; M. Iqbal Ibrahim Hamdani; Mohamad Il Badri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effectiveness of the History Room application as an interactive learning medium to improve learning outcomes in social studies. The research method used the Classroom Action Research (CAR) approach model Kemmis and McTaggart, this study involved 25 students and was conducted in two cycles. Data collection was carried out through initial tests (pre-test) and final tests (post-test) to measure improvements in student learning outcomes. The History Room application, which presents historical material through text, images, and videos, was integrated into classroom learning activities. The results showed a significant increase in students' average scores, from 65.08 in the pre-test to 80.04 in the post-test, with a learning mastery level reaching 88%. These findings indicate that the History Room application successfully creates a student-centered learning atmosphere, encourages independent exploration of historical content, and enhances collaboration between students. Overall, this study concludes that the use of interactive digital media such as History Room is effective in making social studies subjects more interesting and accessible, thereby optimally increasing student engagement and understanding. Keywords: Application, Increase, Student.